System center 2012 R2 virtual machine manager cookbook : over 70 recipes to help you design, configure, and manage a reliable and efficient virtual infrastructure with VNM 2012 R2 /: over 70 recipes to help you design, configure, and manage a reliable and efficient virtual infrastructure with VNM 2012 R2. (2014) - Cardoso, Edvaldo Alessandro
No abstract available